Numerical design of a hot-stretch-reducing process for welded tubes - Rešković, Stoja (Materiali in tehnologije, 2010)
During stretch reducing, steel is submitted to complex stressing and straining processes. This paper gives a theoretical model of a heat-stretch-reducing process for the relation between the tube diameter and the wall thickness. The design is verified by a determination of the number of revolutions of rolls with every caliber for specific tubes on an industrial mill. The control of the rolled-tube dimensions confirmed the accuracy of the design.
Keywords: preoblikovanje kovin; vroča raztezna redukcija; varjenje; cevi; numerične metode